Breeding Season Survival and Reproduction in a High-Density Bobwhite Population: A case study - William E. Palmer; Shane D Wellendorf; D. Clay Sisson (National Quail Symposium Proceedings, 2022)
The demographic behavior of northern bobwhite (Colinus virginianus; hereafter, bobwhite) populations at high densities could provide important insights into why bobwhite populations fluctuate. Therefore, we documented breeding season demographics of bobwhites to understand how prebreeding density influenced reproductive effort and postbreeding density on an intensively managed property in Leon County, Florida, USA, 2002–2006. We estimated prebreeding bobwhite density each April using multi-observer strip-transects and postbreeding densities each November using covey call grid surveys. We radio-tagged 217 bobwhites in March and located bobwhites at least 5 days/week, 15 April–30 September to determine vital rates. Prebreeding density ranged from 1.5–8.6 birds/ha, peaking in 2002, declining through 2005, then increasing in 2006. Breeding season survival was 0.55, 0.17, 0.20, and 0.59, and nesting rate was 0.47, 0.67, 0.80 and 0.89, 2002–2005, respectively. Postbreeding density ranged from 5.2–13.6 birds/ha, also peaking in 2002 and declining through 2004 before increasing beginning in 2005 and 2006. High breeding season survival and nesting success (>0.55) resulted in greater chick production during periods of population growth. Nesting rate was inversely related to prebreeding density. Declines in bobwhite nesting rate at high prebreeding densities appeared to regulate population growth near population peaks. Lower adult survival and nesting success appeared to cause population declines. We suggest density-dependent intraspecific competition limited population growth at high bobwhite densities by reducing nesting rate while predation of adults and nests explained population fluctuations.
Keywords: Colinus virginianus; demographics; density; nesting; northern bobwhite; population; quail; reproduction; survival